Clinical implications of incidental venous thromboembolism in cancer patients. Issue 2 (6th February 2020) - Mulder, Frits I.; Di Nisio, Marcello; Ay, Cihan; Carrier, Marc; Bosch, Floris T.M.; Segers, Annelise; Kraaijpoel, Noémie; Grosso, Michael A.; Zhang, George; Verhamme, Peter; Wang, Tzu-Fei; Weitz, Jeffrey I.; et al.
Introduction: In cancer patients, current guidance suggests similar treatment for incidental and symptomatic venous thromboembolism (VTE), mainly based on retrospective data. We aimed to evaluate anticoagulant therapy in cancer patients with incidental and symptomatic VTE. Methods: The Hokusai VTE Cancer Study was a randomised controlled trial comparing edoxaban with dalteparin for cancer-associated VTE. The primary outcome was the composite of first recurrent VTE or major bleeding. Secondary outcomes included major bleeding, recurrent VTE and mortality. Outcomes in patients with incidental and symptomatic VTE were evaluated during the 12-month study period. Results: 331 patients with incidental VTE and 679 patients with symptomatic VTE were enrolled, of whom the index event was confirmed by an independent radiologist. Median durations of anticoagulant treatment were 195 and 189 days, respectively. In patients with incidental VTE, the primary outcome occurred in 12.7% of patients, major bleeding in 6.6% of patients and recurrent VTE in 7.9% of patients. Out of the 26 VTE recurrences in patients with incidental VTE, five (31%) were incidental, seven (44%) were symptomatic and four (25%) were deaths for which pulmonary embolism could not be ruled out. In patients with symptomatic VTE, the primary outcome occurred in 13.8% of patients, major bleeding in 4.9% of patients and recurrent VTE in 10.9% of patients. All-cause mortality was similar in both groups. Conclusion: Clinical adverse outcomes are substantial in both cancer patients with incidental and symptomatic VTE, supporting current guideline recommendations that suggest treating incidental VTE in the same manner as symptomatic VTE. In cancer patients with incidental venous thromboembolism (VTE), the risk of recurrent VTE is substantial despite initiation of anticoagulant treatment. Incidental VTE is a serious condition, which should be treated similar to symptomatic VTE. http://bit.ly/2qM4XUp